Influence of thermal properties on microstructure and adhesive wear behaviour of Al/Al2O3 MMCs - Buytoz, S; Yilmaz, O (Maney Publishing, 2006)
Al alloy and Al/Al2O3 metal matrix composites (MMCs) were fabricated by stir casting. Effect of the thermal properties on wear properties and stir casting parameters on the dry sliding wear resistance of this alloy and Al/Al2O3 MMCs were investigated under 50 - 350 N loads. The temperature was applied at ambient and elevated intervals ( 300 - 475 K), which was controlled by an external heat source. The dry sliding wear tests were performed to investigate the wear behaviour of Al alloy and Al/Al2O3 MMCs against a steel counterface ( DIN 5401) in a block on ring apparatus. The Al/Al2O3 MMCs were prepared by the addition of 5, 10 and 15 vol.-% Al2O3 particulates, and the size of particulates was taken as 16 mm. The wear tests were carried out in an incremental manner, i.e. 300 m per increment and 3000 m in total. The wear test results were used for investigation of the relation between weight loss, microstructure, surface hardness, friction coefficient, particulate percentage and thermal conductivity of Al/Al2O3 MMCs. Finally, it was observed that Al2O3(p) reinforcement is beneficial in increasing the wear resistance of Al/ Al2O3 MMCs. Furthermore, Al2O3 particulates in MMCs tend to reduce the extent of plastic deformation in the subsurface region of the matrix, therefore delaying the nucleation and propagation of subsurface microcracks. On the other hand, it can be seen that the increase in Al2O3 particulates decreased both thermal conductivity and friction coefficient, hence increased the transition load and transition temperature for mild to severe wear during dry sliding wear test.
Keywords: MMCs; stir casting; wear behaviour